Utilization of 4T score to determine the pretest probability of heparin-induced thrombocytopenia in a community hospital in upstate New York - Yazan Samhouri; Mohammad Telfah; Ruth Kouides; Timothy Woodlock (Greater Baltimore Medical Center, 2016)
Background: Thrombocytopenia is common in hospitalized patients. Heparin-induced thrombocytopenia (HIT) is a life-threatening condition which can lead to extensive thrombosis. Diagnosis of HIT relies on clinical suspicion determined by 4T score and immunoassays through testing for anti-PF4/heparin antibodies. Clinical practice guidelines published by the American Society of Hematology in 2013 recommended use of the 4T score before ordering the immunoassays as a measure of pretest probability. The purpose of this study was to evaluate the utilization of 4T score before ordering anti-PF4/heparin antibodies at Unity Hospital. Methods: We did a retrospective chart review for patients who are 18 years or older, admitted to Unity Hospital between July 1, 2013, and December 31, 2014, and had anti-PF4/heparin antibodies ordered. Subjects who had prior history of HIT or had end-stage renal disease on hemodialysis were excluded. After calculating 4T score retrospectively, we calculated the proportion of patients who had 4T score documented prior to ELISA testing and proportion of ELISA tests, which were not indicated due to a 4T score less than or equal to 3 using Minitab 16. Results: Review of 123 patients, with an average age of 69.4 years, showed that testing was indicated in 18 patients. Six subjects had positive results, and testing was indicated in all of them. 4T score was documented in three patients. This quality improvement study showed that 4T score documentation rate at Unity Hospital is 2.4%. Anti-PF4/heparin antibody testing was indicated in 14.6%. This test is being overused in thrombocytopenia work up at Unity Hospital, costing $9,345. The topic was reviewed for residents. A prompt and calculator for 4T score were added to electronic medical records before ordering the test as a step to improve high value care.